Who is Jeff Kinney? - Kinney, Patrick; Hinderliter, John (2015)
"Even as a kid, everyone thought Jeff Kinney was talented. People loved his drawings, and when he went to college, his comic strip Igdoof was so popular that it spread to other universities! Still, Jeff faced challenges. His cartoons were rejected by syndicates that claimed his art was unprofessional. Then, an idea struck: Jeff would write a journal from the perspective of a child, illustrated with doodles just like a kid might do. And so, the Diary of a Wimpy Kid series was born--and it was a hit! In this biography, Jeff's brother, Patrick Kinney, provides a knowledgeable look at the life of this best-selling author/illustrator. From Jeff's childhood pranks to his job developing online games, kids will love the chance to learn more about the creator of the popular Wimpy Kid books"--
Keywords: Authors, American -- Biography -- Juvenile literature; Children's stories -- Authorship -- Juvenile literature; Cartoonists -- Biography -- Juvenile literature; JUVENILE NONFICTION / Biography & Autobiography / Literary; JUVENILE NONFICTION / Art / Cartooning; JUVENILE NONFICTION / People & Places / United States / General